CONSEQUENCES OF EMPLOYEE’S CUSTOMER ORIENTATION IN PUBLIC SERVICES - Andrada IACOB (Management & Marketing)
The goal of this paper is to explore the consequences of employee’s customer orientation in public services organizations. We will start with a literature review of the theory of customer orientation measurement and the consequences of this orientation at organizational and individual level. Then, the research methodology and results are presented. Conclusions, research limitations and future directions are included at the end of the paper. We identified positive direct effects of the employee customer orientation on organizational commitment and organizational identification, but no significant direct relationship with job satisfaction.